Prospecção de substâncias anti histoplasma capsulatum nas formas planctônica e biofilme e análise proteômica - Midoricava, Luana Rossi Oliveira [UNESP] (2015)
Histoplasma capsulatum var. capsulatum is a dimorphic fungi that causes Histoplasmosis, a systemical fungal disease that is a major health problem worldwide. Infection occurs by inhalation of infective propagules from the environment. The biofilm formation by this fungi was characterized recently, however little is known about the mechanisms involved in their formation. In this case, studies with proteomic approaches would be of fundamental importance for understanding the difference between the planktonic and biofilm forms. The antifungal agents used in conventional therapy are not effective against biofilms, in addition, high doses of these drugs can be toxic to patients. This study aimed to verify the anti-Histoplasma activity of 93 compounds derived from chalcones and protocatechuic acid; characterize the biofilm formation by the clinical isolate H. capsulatum 317 and discover new anti-biofilm compounds searching for a mechanism of action by differential proteomics analysis, comparing the treated and untreated biofilms. Susceptibility tests were performed according to the document M27- A3, proposed by the CLSI (2008). The biofilms were formed in BHI broth supplemented and metabolic activity was determined by the XTT reduction assay. For the characterization of biofilm formation and action of the compound, was used the scanning electron microscopy (SEM) and confocal microscopy, while the mass of the biofilm and the extracellular matrix were quantified by crystal violet and safranin. Lastly was performed the analysis of the protein profile of biofilms with and without treatment. The best minimum inhibitory concentration values (MIC) were obtained for six derivatives of chalcones (T50, C3, E2A, F2A, T18A and T46A) and nonyl protocatechuate (MIC = 3.9 mg/L). The clinical isolate H. capsulatum EH317 was able to form biofilms in vitro after 96 hours. After 96 hours, the biofilm ...